2019
DOI: 10.3390/s19153387
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Shunt Stiffness in Rhombic Piezoelectric Stack Transducer with Hybrid Negative-Impedance Shunts: Theoretical Modeling and Stability Analysis

Abstract: Negative-capacitance shunted piezoelectric polymer was investigated in depth due to its considerable damping effect. This paper discusses the novel controlled stiffness performance from a rhombic piezoelectric stack transducer with three hybrid negative-impedance shunts, namely, negative capacitance in series with resistance, negative capacitance in parallel with resistance, and negative inductance/negative capacitance (NINC) in series with resistance. An analytical framework for establishing the model of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…The intensity of the peaks established at low weight percentages used is the minimum due to the small amounts of BaTiO 3 and PZT added to the composite fibers, and the intensity of the revealed peaks increases with the increase in weight percentage. As a consequence, the investigation revealed that the characteristic peak of BaTiO 3 occurred at 2θ = 32.17° (110) [ 41 ], and the increase in the intensity of the PZT peaks at 2θ = 32° (110) and 22° (101) showed an increased amount of PZT in the fiber structure [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of the peaks established at low weight percentages used is the minimum due to the small amounts of BaTiO 3 and PZT added to the composite fibers, and the intensity of the revealed peaks increases with the increase in weight percentage. As a consequence, the investigation revealed that the characteristic peak of BaTiO 3 occurred at 2θ = 32.17° (110) [ 41 ], and the increase in the intensity of the PZT peaks at 2θ = 32° (110) and 22° (101) showed an increased amount of PZT in the fiber structure [ 42 ].…”
Section: Resultsmentioning
confidence: 99%